Individual Evaluation of Judges in Germany - Johannes Riedel (Oñati Socio-Legal Series)
In Germany, with the exception of the five federal supreme courts, court organization is a responsibility of the Länder (federal states). In some of the Länder, so-called employee profiles (“Anforderungsprofile“) have been established for judicial office. These lists attempt to describe criteria for certain judicial positions. They are applied in the process of promotion but also serve as an indicator for initial appointment.